Cardiovascular Parameters in a Swine Model of Normobaric Hypoxia Treated With 5-Hydroxymethyl-2-Furfural (5-HMF) - Mahon, Richard Thomas; Ciarlone, Geoffrey E.; Roney, Nicholas G.; Swift, Joshua M. (Frontiers in Physiology, 2019)
INTRODUCTION: The consequences of low partial pressure of O2 include low arterial O2 saturations (SaO2), low blood O2 content (CaO2), elevated mean pulmonary artery pressure (PAP) and decreased O2 consumption VO2. 5-hydroxymethyl-2-furfural (5-HMF) binds to the N-terminal valine of hemoglobin (HgB) and increases its affinity to O2. We used an instrumented, sedated swine model to study the effect of 5-HMF on cardiovascular parameters during exposure to acute normobaric hypoxia (NH). METHODS: Twenty-three sedated and instrumented swine were randomly assigned to one of three treatment groups and received equal volume of normal saline (VEH), 20mg/kg 5-HMF (5-HMF-20) or 40mg/kg 5-HMF (5-HMF-40). Animals then breathed 10% FiO2 for 120 minutes. Parameters recorded were Cardiac Output (CO), Mean Arterial Blood Pressure (MAP), Heart Rate (HR), Mean Pulmonary Artery Pressure (PAP), SaO2 and saturation of mixed venous blood (SvO2). The P50 was measured at fixed time intervals prior to and during NH. RESULTS: 5-HMF decreased P50. In the first 30 minutes of NH, treatment with 5-HMF-20 and 5-HMF-40 resulted in a 1) significantly smaller decrement in SaO2 and SvO2, 2) significantly lower HR and CO, and 3) smaller increase in PAP compared to VEH. In the 120 minutes of NH there was a trend towards improved mortality with 5-HMF treatment. CONCLUSIONS: 5-HMF treatment